Comparative Analysis of Consumers Behavior Who Shop for Daily Food in Modren and Traditional Market - Mayang Kurniawan; Mitra Musika Lubis; Endang Sari Simanullang (Universitas Medan Area, 2020)
This study was conducted to determine how the differences in consumer behavior and factors that influence behavior consumers buy daily staple food in the Modern Market and Traditional Market. The sampling method is done by simple ramdom sampling. Respondents in this study is that consumers buy daily staple food in the Modern Market and Traditional Market. Samples taken are as many as 72 samples of daily staple food consumers. The data collected are primary data and secondary data. The analytical method used is Mann-Whitney Test and ordinal regression with 18 SPSS software tools. Based on test results Mann-Whitney Test showed: indicate a significant difference consumer behavior buy daily staple food in the Modern Market and Traditional Market to the value Asymp. Sig 0,001 (<0,005), where the modern market that has a higher value than Traditional Market. Based on test results ordinal regression showed: factors affecting behavior consumers buy daily staple food in the Modern Market and Traditional Market is price, locations, product quality, consumer satisfaction. Factors individual and product information has no affecting behavior consumers buy daily staple food in the Modern Market and Traditional Market.Keywords: modern market; traditional market; consumer behavior.